THE EFFECT OF DIFFERENCE STRATEGY, MARKET ORIENTATION, AND PRICE PERCEPTION ON COMPETITIVE ADVANTAGE IN THE MARKETPLACE - Nuning Nurna Dewi; Ida Putri Nur Cahyani; Nikma Yucha (Ecopreneur.12, 2022)
This study aims to determine the effect of differentiation strategy, market orientation, and price perceptions on competitive advantage in the marketplace. This research was conducted on students of the Faculty of Economics and Business, with a population of 541 students. The sampling technique for this study used nonprobability sampling with the purposive sampling method. The data analysis technique used in this study is Multiple Linear Regression Analysis. Based on the results of data analysis, it was found that the differentiation strategy partially had a positive and insignificant effect on competitive advantage with value. Meanwhile, the market orientation variable partially has a positive and significant impact on competitive advantage. And the price perception variable partially has a positive and significant impact on competitive advantage. Thus it can be concluded that the differentiation strategy, market orientation, and price perception simultaneously positively and significantly impact competitive advantage. From the analysis results, the coefficient of determination (R2) is 0.405. This means that the three variables of differentiation strategy, market orientation and price perception contribute 40.5% to competitive advantage. In contrast, the remaining 59.5% is a contribution/contribution of other variables not observed in this study.